HASIL Asystasia gangetica (L.) subsp. Micrantha PADA PEMOTONGAN KEDUA YANG DIBERI CAMPURAN PUPUK KANDANG KAMBING DAN LIMBAH ANGGUR - Robbani M. A.; N. G. K. Roni; N. N. C. Kusumawati (Fakultas Peternakan Universitas Udayana, 2025)
This study aims to evaluate the yield of Asystasia gangetica (L.) subsp. Micrantha treated with a mixture of goat manure and grape waste. The research was conducted in Sading Village, Mengwi District, Badung Regency, Bali Province, over a period of 12 weeks. The study employed a Completely Randomized Design (CRD) consisting of six treatments and five replications, as follows: treatment A = 0% goat manure + 0% grape waste, B = 0% goat manure + 100% grape waste, C = 100% goat manure + 0% grape waste, D = 75% goat manure + 25% grape waste, E = 50% goat manure + 50% grape waste, and F = 25% goat manure + 75% grape waste. The observed variables included: dry weight of leaves, dry weight of stems, dry weight of roots, total forage dry weight, the ratio of leaf dry weight to stem dry weight, and the ratio of total forage dry weight to root dry weight. The results showed that the mixture of goat manure and grape waste in treatment E significantly increased leaf dry weight, stem dry weight, total forage dry weight, and the ratio of total forage dry weight to root dry weight of Asystasia gangetica (L.) subsp. Micrantha during the second harvest. Based on these findings, it can be concluded that the combination of goat manure and grape waste improves the yield of Asystasia gangetica, with the best results observed in the 50% goat manure + 50% grape waste mixture during the second harvest. ABSTRAK Penelitian ini bertujuan untuk mengetahui hasil Asystasia gangetica (L.) subsp. Micrantha yang diberi campuran pupuk kandang kambing dan limbah anggur. Penelitian ini berlokasi di Desa Sading, Kecamatan Mengwi, Kabupaten Badung, Provinsi Bali yang berlangsung selama 12 minggu. Penelitian ini menggunakan rancangan acak lengkap (RAL) yang terdiri dari 6 perlakuan dan 5 pengulangan yaitu; perlakuan A = 0% pupuk kandang kambing + 0% limbah anggur, B = 0% pupuk kandang kambing + 100% limbah anggur, C = 100% pupuk kandang kambing + 0% limbah anggur, D = 75% pupuk kandang kambing + 25% limbah anggur, E = 50% pupuk kandang kambing + 50% limbah anggur, F = 25% pupuk kandang kambing + 75% limbah anggur. Variabel yang diamati meliputi; berat kering daun, berat kering batang, berat kering akar, berat kering total hijauan, nisbah berat kering daun dengan berat kering batang dan nisbah berat kering total hijauan dengan berat kering akar. Hasil penelitian menunjukkan campuran pupuk kandang kambing dengan campuran limbah anggur pada perlakuan E dapat meningkatkan berat kering daun, berat kering batang, berat kering total hijauan, dan nisbah berat kering total hijauan dengan berat kering akar Asystasia gangetica (L.) subsp. Micrantha pada pemotongan kedua. Berdasarkan hasil penelitian dapat disimpulkan campuran pupuk kandang kambing dan limbah anggur meningkatkan hasil Asystasia gangetica, dan campuran 50% pupuk kandang kambing + 50% limbah anggur memberikan hasil terbaik pada pemotongan kedua.